2020
DOI: 10.1093/ajcn/nqz271
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic effects of a prolonged, very-high-dose dietary fructose challenge in healthy subjects

Abstract: Background Increased fructose intake has been associated with metabolic consequences such as impaired hepatic lipid metabolism and development of nonalcoholic fatty liver disease (NAFLD). Objectives The aim of this study was to investigate the role of fructose in glucose and lipid metabolism in the liver, heart, skeletal muscle, and adipose tissue. Methods Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…A systematic review and meta-analysis of six observational studies and 21 intervention studies concluded that there was insufficiently robust evidence available to demonstrate that high intake of fructose, HFCS, or sucrose is associated with a higher incidence of NAFLD and suggested that the relationship between fructose intake and NAFLD could be confounded by excessive energy intake [ 88 ]. In accordance with this, a recent short-term interventional study found that a high-fructose diet (150 g a day for 8 weeks) in an isocaloric context does not have negative health impacts on weight, liver health, cholesterol, insulin sensitivity, or glucose/blood sugar tolerance in healthy individuals [ 89 ]. In this trial with healthy individuals, no change in intramuscular or intrahepatic fat was observed, but there were higher levels of serum triglycerides and DNL.…”
Section: Nutrition and Nafldmentioning
confidence: 70%
See 2 more Smart Citations
“…A systematic review and meta-analysis of six observational studies and 21 intervention studies concluded that there was insufficiently robust evidence available to demonstrate that high intake of fructose, HFCS, or sucrose is associated with a higher incidence of NAFLD and suggested that the relationship between fructose intake and NAFLD could be confounded by excessive energy intake [ 88 ]. In accordance with this, a recent short-term interventional study found that a high-fructose diet (150 g a day for 8 weeks) in an isocaloric context does not have negative health impacts on weight, liver health, cholesterol, insulin sensitivity, or glucose/blood sugar tolerance in healthy individuals [ 89 ]. In this trial with healthy individuals, no change in intramuscular or intrahepatic fat was observed, but there were higher levels of serum triglycerides and DNL.…”
Section: Nutrition and Nafldmentioning
confidence: 70%
“…High consumption of simple, high-glycaemic-index carbohydrates is associated with NAFLD [ 70 ]. Therefore, lower consumption of sugars should be advised, especially in high-calorie diets, although the pernicious effect of carbohydrates is more controversial in isocaloric or hypocaloric diets [ 89 , 90 ]. Fructose, as a paradigmatic example of this type of carbohydrate, deserves special attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of a difference between glucose and fructose, but higher hepatic TG levels in the hypercaloric condition compared with the isocaloric condition confirm the notion that it is particularly the energy intake, rather than specific effects of fructose compared with glucose that results in the adverse metabolic effects. Indeed, a recent human study showed also overall lack of effects by high fructose intake (Smajis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…( 79 ) A recent study in 10 healthy subjects, however, with excess isocaloric fructose consumption for 8 weeks showed no detrimental metabolic effects including the liver. ( 80 ) This raises some doubts as to whether fructose indeed damages the human liver to promote NAFLD. Wheat amylase trypsin inhibitors, a common dietary wheat component, activates intestinal macrophages ( 81 ) and has also been linked to experimental NAFLD as its consumption aggravates liver and AT inflammation.…”
Section: Gastrointestinal Cues Fueling Nafld: From Intestinal Microbimentioning
confidence: 99%